Graphene-Carbon Nanotube Hybrids for Energy and Environmental Applications - Fan, Wei.; Zhang, Longsheng; Liu, Tianxi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book describes various carbon nanomaterials and their unique properties, and offers a detailed introduction to graphene-carbon nanotube (CNT) hybrids. It demonstrates strategies for the hybridization of CNTs with graphene, which fully utilize the synergistic effect between graphene and CNTs. It also presents a wide range of applications of graphene-CNT hybrids as novel materials for energy storage and environmental remediation. Further, it discusses the preparation, structures and properties of graphene-CNT hybrids, providing interesting examples of three types of graphene-CNT hybrids with different nanostructures. This book is of interest to a wide readership in various fields of materials science and engineering.
Introduction -- Structures and properties of carbon nanomaterials -- Strategies for the hybridization of carbon nanotubes with graphene -- Application of graphene-carbon nanotube hybrids for energy storage -- Application of graphene-carbon nanotube hybrids for environmental remediation -- Summary.
Keywords: Nanotechnology; Energy storage; Electrochemistry; Pollution; Nanotechnology; Mechanical and Thermal Energy Storage; Electrochemistry; Pollution